PENGARUH DISIPLIN KERJA, KEPUASAN KERJA DAN KOMITMEN ORGANIZATIONAL TERHADAP KINERJA PEGAWAI - Euis Novianti; Endro Sukotjo; Nasrul Nasrul (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2018)
This study aims to examine and analyze empirically the influence of work discipline, job satisfaction and organizational commitment on employee performance at the Regional Employment Agency of Muna Regency. The population in this study were all employees at the Regional Civil Service Agency of Muna Regency, amounting to 58 people. This study uses Multiple Linear Regression analysis.The results of the study show that: (1) Work discipline, job satisfaction and organizational commitment have a positive and significant effect on the performance of employees in the Regional Employment Agency of Muna Regency. (2) Work discipline has a positive and significant effect on employee performance at the Regional Personnel Agency of Muna Regency. (3) Job satisfaction has a positive and significant effect on employee performance at the Regional Personnel Agency of Muna Regency. (4) Organizational commitment has a positive and significant effect on employee performance. Keywords: work discipline, job satisfaction, organizational commitment and employee performance